The unadoptables - Tooke, Hana (Viking, 2020)
In all the years that Elinora Gassbeek has been matron of the Little Tulip Orphanage, not once have the Rules for Baby Abandonment been broken. Until the autumn of 1880, when five babies are left in outrageous circumstances; one in a tin toolbox, one in a coal bucket, one in a picnic hamper, one in a wheat sack, and finally, one in a coffin-shaped basket. Those babies were Lotta, Egg, Fenna, Sem, and Milou. And although their cruel matron might think they're "unadoptable," they know their individuality is what makes them special--and so determined to stay together. When a most sinister gentleman appears and threatens to tear them apart, the gang make a daring escape across the frozen canals of Amsterdam. But is their real home--and their real family--already closer than they realize?--